“Phage Transplantation in Allotransplantation”: Possible Treatment in Graft-Versus-Host Disease? - Górski, Andrzej; Jończyk-Matysiak, Ewa; Międzybrodzki, Ryszard; Weber-Dąbrowska, Beata; Borysowski, Jan (Frontiers in Immunology, 2018)
Graft-versus-host disease, both acute and chronic (aGvHD, cGvHD) remains a major complication in patients undergoing hematopoietic cell transplantation (HCT) and a significant therapeutic challenge, as many patients do not respond adequately to presently available therapy. Increasing antimicrobial resistance has greatly revived interest in using bacterial viruses (phages) to combat antibiotic-resistant bacteria. In recent years evidence has accumulated indicating that phages also have anti-inflammatory and immunomodulatory activities. This article suggests how these anti-bacterial and immunomodulatory activities of phages may be translated into a novel treatment of acute GvHD.